The effect green YF3:ER3+,YB3+ phosphor on luminous flux and color quality of multi-chip white light-emitting diodes - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Thuc Minh Bui; Anh Tuan Le (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The purpose of this paper is to demonstrate the advantages of the green phosphor YF3:Er3+,Yb3+ combined with multi-chip package to the enhancement of lighting efficiency of modern WLEDs. In an effort to improve the quality of WLEDs and create a new generation of lighting device, green phosphor YF3:Er3+,Yb3+ is added into the phosphor compounding of the WLED package to improve the color quality and lighting capacity. Through experiments, WLEDs with YF3:Er3+,Yb3+ green phosphor has shown improved results in lighting performance specifically in color homogeneity and light output of WLEDs in the ACCT range from 5600-7000 K. However, the color quality scale (CQS) declines gradually. Therefore, if the appropriate concentration and size of YF3:Er3+,Yb3+ are determined, the performance of MCW-LEDs will be enhanced and become more stable.